TRANSFORMING DIGITAL BUSINESS MODEL INNOVATION (DBMI) TO ENHANCE SME BUSINESS PERFORMANCE IN MALAYSIA: A CUSTOMER PERSPECTIVE - Norliza Ramli; Hazliza Haron, (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2025)
Amidst the contemporary digital scene, realizing Digital Business Model Innovation (DBMI) is an indispensable strategy for SMEs in Malaysia's F&B landscape to profoundly elevate their performance and ensure they remain competitive. This study delves into the pivotal impact of digital literacy, product innovation, service convenience, and digital interaction quality, with customer engagement serving as a crucial mediator. By analysing data from 300 SME customers through Multiple Regression Analysis, we uncover vital performance drivers, backed by Pearson Correlation and Factor Analyses to confirm the relationships and constructs at play. The results demonstrate that digital literacy and product innovation markedly boost customer engagement, establishing a vital connection to enhanced business outcomes. Furthermore, service convenience and digital interaction quality emerge as indispensable components, cultivating customer loyalty, advocacy, and seamless experiences. These insights emphasize the pressing necessity for SMEs to implement customer-centric digital strategies, harnessing innovation and exceptional digital interactions to attain sustainable growth, bolster market resilience, and secure a competitive advantage in an ever-evolving digital marketplace.